1995
DOI: 10.1515/hfsg.1995.49.6.575
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Analysis of Wood/Aminoplastic Adhesives Joints Cross-Linking - UF, MUF, PMUF

Abstract: Non-isothermal and isothermal thermomechanical analysis (TMA) of the cross-linking and hardening of wood joints bonded with urea-formaldehyde (UF), melamine-urea-formaldehyde (MUF), and phenol-melamine-urea-formaldehyde (PMUF) resins was carried out, allowing the determination of the variation of physical properties of these thermosetting adhesives in situ in the wood joint. Gelling temperature, hardening and vitrification temperature and temperature at which relative elastic moduli reach their maximum were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Thus, the explanation of the formation of a multistep modulus increase curve for a phenolic resin can be ascribed to a series of different related and unrelated causes, namely, (1) the OCH 2 OCH 2 O 3 OCH 2 O rearrangement; (2) the important linear growth of the polymer before the start of tridimensional crosslinking, leading to the initial formation of entanglement networks; and (3) the relationship between the storage and viscous components GЈ and GЉ of the modulus as a function of temperature, time, and reaction advancement, which is related to the first 2 causes outlined. The accepted methods of calculating the gel point and gel temperature of a polycondensation resin or from (1) the single peak of the first derivate of the modulus increase curve (an approach nonetheless conceptually incorrect, as this would represent in a single step curve the start of vitrification 1 and not the gel point); or from (2) the start of the uprise of the modulus increase curve are incorrect (the former), and the second still acceptable in resins in which the entanglement effect is small or it is not present. In resin systems in which the entanglement effect is, instead, of importance and multisteps modulus increase curves are obtained, the question of what is the gel point in such systems had to be addressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the explanation of the formation of a multistep modulus increase curve for a phenolic resin can be ascribed to a series of different related and unrelated causes, namely, (1) the OCH 2 OCH 2 O 3 OCH 2 O rearrangement; (2) the important linear growth of the polymer before the start of tridimensional crosslinking, leading to the initial formation of entanglement networks; and (3) the relationship between the storage and viscous components GЈ and GЉ of the modulus as a function of temperature, time, and reaction advancement, which is related to the first 2 causes outlined. The accepted methods of calculating the gel point and gel temperature of a polycondensation resin or from (1) the single peak of the first derivate of the modulus increase curve (an approach nonetheless conceptually incorrect, as this would represent in a single step curve the start of vitrification 1 and not the gel point); or from (2) the start of the uprise of the modulus increase curve are incorrect (the former), and the second still acceptable in resins in which the entanglement effect is small or it is not present. In resin systems in which the entanglement effect is, instead, of importance and multisteps modulus increase curves are obtained, the question of what is the gel point in such systems had to be addressed.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Recent work on the polycondensation reaction with formaldehyde and other hardeners of polyflavonoid tannins, however, casts some doubts on this approach. 4 This is the consequence of the multistep modulus increase curves, the increase in modulus caused by the polymer reaching a critical, temperature-and concentration-dependent length sufficient to yield an entanglement network?…”
Section: Introductionmentioning
confidence: 99%
“…Before building a CHT diagram, a few rules need to be defined: The total modulus curve obtained at constant heating rates can be used to determine the gel point of the system and the start of vitrification according to known techniques 3,17 as well as the peaks of the modulus curve first derivate. 7,12,17 However, while no controversy exists as regards the site representing the start of vitrification on TMA modulus curves, 3 the real position of the gel point on the modulus curve is still a subject for some debate.…”
Section: Tma Determination Of Average Number Of Degrees Of Freedom Ofmentioning
confidence: 99%
“…7,12,17 However, while no controversy exists as regards the site representing the start of vitrification on TMA modulus curves, 3 the real position of the gel point on the modulus curve is still a subject for some debate. For these reasons, the CHT diagrams of the UF adhesive/ wood system were then constructed using all the different approaches possible to the gel point to check all the possibilities.…”
Section: Tma Determination Of Average Number Of Degrees Of Freedom Ofmentioning
confidence: 99%
“…The chemical curing can be monitored using differential thermal analysis (DTA) [19 -21] or differential scanning calorimetry (DSC) [22 -25]. The development of bond strength can be followed by dynamic mechanical analysis (DMA) [26 -29], thermal mechanical analysis (TMA) [30,31], torsional braid analysis (TBA) [32 -34], or by the so-called automatic bonding evaluation system (ABES) [35,36] as used in the study reported here. Thermal scanning rheometry also can monitor the curing behavior of thermosetting resins [37 -39] and was used in the work described here.…”
Section: Downloaded By [Gazi University] At 16:11 27 December 2014mentioning
confidence: 99%